2022
DOI: 10.3390/pr10122597
|View full text |Cite
|
Sign up to set email alerts
|

Safety-Risk Assessment for TBM Construction of Hydraulic Tunnel Based on Fuzzy Evidence Reasoning

Abstract: Due to multiple factors influencing the construction safety of TBM hydraulic tunnels, risk assessment is a critical point of a construction management plan to avoid possible risks. In this paper, a safety-risk evaluation index system of TBM construction for hydraulic tunnels is built based on the identification and analysis of possible sources of risk in techniques, geologic, equipment, management, and accidents. Considering the influence of factors such as the experience level and the expertise of decision ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the above Equations, m n i denotes the basic fuzzy confidence value of risk index r i at the fuzzy risk level of FH n , m H i denotes the uncertain risks due to lack of information, which includes can be presented in Equations 9-12 (60,61).…”
Section: Figurementioning
confidence: 99%
“…In the above Equations, m n i denotes the basic fuzzy confidence value of risk index r i at the fuzzy risk level of FH n , m H i denotes the uncertain risks due to lack of information, which includes can be presented in Equations 9-12 (60,61).…”
Section: Figurementioning
confidence: 99%
“…. ., L), the weights of these indexes r i are ω i and that every risk index follows the fuzzy belief model FBS(D i ) = FH n , β n i , we can calculate the mass number of each risk index, as presented in Formulas ( 5)-( 8) [60].…”
Section: Safety Risk Duringmscubmentioning
confidence: 99%
“…In the above formulas, m n i denotes the basic fuzzy belief value of risk index r i at the fuzzy risk level of FH n , and m H i denotes the uncertain risks due to a lack of information, which includes m H i and m H i . Let m n I(i) denote the belief degree to the nth evaluation level of an upper-level risk index that the first i lower-level indexes support; m H I(i) denotes the retained probability after all the first i lower-level risk indexes have been assigned to all the evaluation levels; thus, the recursive processes of m n I(i) and m H I(i) are expressed in Formulas ( 9)-( 12) [60,61].…”
Section: Safety Risk Duringmscubmentioning
confidence: 99%
“…These methods include shallow buried asymmetric tunnels, deep buried tunnels in weak surrounding rocks, landslide geological body tunnels, etc., which can effectively prevent water seepage and support excavations while also protecting the environment and construction safety 18 . Based on the control of tunnel construction progress, some researchers put forward the research ideas, technical routes and construction methods of underground tunnel-group construction, developed the online monitoring system of underground tunnel-group construction progress, and applied it to hydropower stations, water diversion and other large-scale water conservancy projects, and achieved good results in improving the construction progress 19 . Some researchers have carried out the comparison between the traditional drilling and blasting method and the full-face tunneling method, and concluded that the tunneling speed of TBM is much higher than that of drilling and blasting method.…”
Section: Introductionmentioning
confidence: 99%